International librarianship : surveys of recent developments in developing countries and in advanced librarianship submitted to the 1971 IFLA Pre-Session Seminar for Developing Countries sponsored by Unesco, Liverpool City Libraries, August 24-September 1, 1971 - Chandler, George; Unesco (London : Library Association, 1972)
The book examines the condition of libraries in the developing countries and how best to overcome some of the challenges.
Includes bibliographical references and index.
usc 14/01/2019
Loans
Keywords: Library science; Comparative librarianship; Developing countries